Contextualising implementation interventions for promoting outpatient integrative Chinese–western oncology service delivery and utilisation in Hong Kong: a Delphi study - Leonard Ho; Ming Hong Kwong; Angus S. C. Li; Fai Fai Ho; Claire C. W. Zhong; Charlene H. L. Wong; Vincent C. H. Chung (BMC Complementary Medicine and Therapies)
Abstract Introduction The rapidly rising incidence and prevalence of cancer pose a financial burden on Hong Kong’s health system. This study aimed to co-create an outpatient integrative oncology (IO) service delivery model for the territory that bridges the District Health Centres (DHCs; local coordinators for medical and social service providers), private traditional Chinese medicine practitioners (TCMPs), and private oncologists and to establish stakeholder-recommended implementation interventions (IIs) for promoting service delivery and utilisation. Methods We conducted individual semi-structured contextual interviews to develop a preferred outpatient model that would enable DHC-based IO interprofessional collaborations and to refine relevant IIs developed for facilitating the implementation of the model. Then, we conducted a Delphi survey to contextualise and finalise the IIs using the APEASE criteria. Results After interviewing 11 local stakeholders, a model was proposed that IO specialist nurses in DHCs would coordinate referrals between private TCMPs and oncologists and evaluate service delivery. Thirty-six IIs were refined to support model implementation. This model presented the possible role of cancer nurse specialists in leading and coordinating interprofessional cancer care between traditional and conventional medicine. In the Delphi study, 21 local stakeholders achieved positive consensus on 35 IIs (agreement 76.2–100%). Affordability was the most critical criterion in determining the recommendation of IIs. Conclusions Along with the 35 local stakeholder-recommended IIs, our proposed nurse-led model provided insights into forging the partnership between the nurse specialists, private TCMPs, and oncologists to provide outpatient IO services. Further research is expected to seek opinions from policymakers regarding the potential administrative implementation determinants.